White Blood Cell Count and Serum Cytokine Profile in Tropical Hardwood Workers in Kumasi - Isaac Ekow Ennin; Margaret Agyei Frempong; Daniel Dodoo; Francis A. Yeboah; Raymond Saa-Eru Maalman (Mediators of Inflammation)
Background. Occupational exposure to wood dust particles has long been reported of its associated varying degrees of negative health effects due to different extractive chemicals present in the various timber species. However, tropical hardwood is also reported to have higher levels of extractive chemicals of antihistamine, antioxidant, and anti-inflammatory properties. In Ghana, woodworkers have for years been exposed to wood dust from mixed tropical hardwood species, with little or no protective equipment such as nose masks, yet with less significant respiratory conditions. This study seeks to investigate the serum cytokine profile in tropical hardwood workers in Kumasi to provide a better understanding of the immunoregulatory pattern activated in the woodworkers. Method. The study was carried out among woodworkers, teachers, and security men located in Kumasi. A cross-sectional sampling of adult male workers was selected to participate in the study (86 woodworkers and 89 nonwoodworkers). Participants donated blood collected by venepuncture into EDTA tubes and spun to separate serum for cytokine assay. Cytokines including IFN-gamma, IL-1β, IL-2, IL-4, IL-6, IL-10, IL-12, IL-13, and IL-17 were assayed using the Human Premixed Multianalyte Kit (R&D System, Inc., Minneapolis, USA) following the manufacturer’s procedure. The cytokine levels were quantified using the Luminex∗200 analyser. Results. The mean concentration levels for the various cytokines were significantly different (p<0.05) between woodworkers and nonwoodworkers except IL-2. There were significantly increased levels of Th1 and Th2 cytokines expressed in the woodworkers more than the nonwoodworkers. Conclusions. The results from this study reveal that exposed woodworkers of mixed tropical hardwood species show a high level of Th1 and Th2 cytokines in their serum than nonwoodworkers.